مسلح تصادم اور تشدد کے حالات میں قدرتی ماحول کا تحفظ اور اسلامی تعلیمات: تحقیقی جائزہ: Protection of the Natural Environment in The Situation of Armed Conflict and Violence and Islamic Teachings Research Review - Dr Hafiza Fariza Danish, (Al Manhal Research Journal, 2025)
The greatest service to humanity is to make the earth red with the blood of those oppressors and to save the oppressed and helpless servants of Allah from the evil of those corrupters and seditionists who have become the people of Satan and the children of Adam (peace be upon him). But they reveal the troubles of moral, spiritual and material destruction. Those people are not actually human beings who deserve human sympathy, but they are devils in human clothes and real enemies of humanity, with whom real sympathy is to erase their evil from the face of humanity like a wrong letter. They lose their right to life by their actions. They, and those who help them to perpetuate their evil, have no right to live in the world. They are, in fact, an organ of the human body, which is filled with poisonous and irregular matter, the remaining of which may cause the death of the whole body. Therefore, the requirement of wisdom and expediency is that this corrupt and corrupt organ should be cut off and thrown away. In this article, human behavior is discussed in the light of Islamic teachings on the protection of the natural environment in situations of armed conflict and violence.